2021
DOI: 10.1002/tesq.3044
|View full text |Cite
|
Sign up to set email alerts
|

Queer is as Queer Does: Queer L2 Pedagogy in Teacher Education

Abstract: What does it mean to queer the L2 classroom and why does it matter? Building on inclusive pedagogical approaches, this paper considers what queering looks like/sounds like/feels like in the context of two case study classrooms where language teachers learned about Teaching Proficiency Through Reading and Storytelling (TPRS) methods in a novice Mandarin language context. Data include recorded videos and transcriptions, focus groups, fieldnotes, and survey responses. We analyze practice from these two workshops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The qualitative data from the DR audio recordings were analyzed via descriptive coding (Saldaña, 2021) and by clustering codes into two themes, namely, typical requirement of DR (e.g., P-E-E-R and C-R-O-W-D) and personal ideas of parents/siblings (e.g., response to the answers of ADHD children; Cahnmann-Taylor et al, 2022). The data were coded by two well-trained research assistant and intercoder reliability test showed a high reliability ( r = .97) among all audio recordings, indicating that the coding results should be acceptable (Belotto, 2018; O’Connor & Joffe, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The qualitative data from the DR audio recordings were analyzed via descriptive coding (Saldaña, 2021) and by clustering codes into two themes, namely, typical requirement of DR (e.g., P-E-E-R and C-R-O-W-D) and personal ideas of parents/siblings (e.g., response to the answers of ADHD children; Cahnmann-Taylor et al, 2022). The data were coded by two well-trained research assistant and intercoder reliability test showed a high reliability ( r = .97) among all audio recordings, indicating that the coding results should be acceptable (Belotto, 2018; O’Connor & Joffe, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Not only do these studies fail to present a discussion on how gender might possibly relate to such topics, but they also assume an approach that considers gender from a biological and binary view that perceives learners as either female or male. Gender as a non-binary, social construct is being widely discussed by applied linguistics scholars internationally, especially more recently in relation to the work of scholars on gender and sexual identities from the perspectives of queer theory and queer pedagogy (e.g., Cahnmann-Taylor et al, 2022; Nelson, 2006; Paiz, 2019). While we believe Turkey has a long way to go in terms of LGBTQ+ rights as well as gender equity, we would like to reiterate our earlier call for more comprehensive, social-justice approaches to learner diversity that consider all gender and sexual identities, as well as cultures, ethnicities, religions, abilities, and other forms of differences that have an impact on the oppression of some while privileging others.…”
Section: Discussion: An Outlook For Future Researchmentioning
confidence: 99%
“…Guijarro-Ojeda et al (2021) stated that the "interrelation of sexual orientation with being foreign language specialists was almost unanimously positive and favored their psychological and teacher wellbeing" (p. 19). This has been evident not only through integrating their gender-transformative causes in to pedagogy or freely expressing their gender identity (Guijarro-Ojeda et al, 2021;Lin et al, 2020) but also through empowering students by representational justice and disrupting heteronormativity (Coleman, 2020), meaningfully engaging them through relatable aspects of gender identity in language education (Cahnmann-Taylor, Coda, & Jiang, 2021), and fostering an inclusive classroom culture (Aquino, 2015).…”
Section: Queering Eltmentioning
confidence: 99%